STILBENOID CONSTITUENTS IN WELWITSCHIA MIRABILIS - Iliya, I.; Tanaka, T.; Murata, H.; Linuma, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Welwitschia mirabilis is an endangered and unique gymnosperm of the Namibian Desert of South West Africa. It is a monotypic member of the Genus Welwitschia. Since its discovery about 140 years ago, very little is known about its chemical constituents. In the present study we report the isolation and structure elucidation of 10 new stilbenoids from the stem and root of the plant along with some known compounds. The structures of the compounds were assigned by spectroscopic analysis